The Critical Thinking in Takhrij Al-Hadith: A Methodological Approach - Mohd Sobri Ellias; Mohamad Naim Fikri bin Norazmi; Mohd Asyran Safwan b. Kamaruzaman; Mohd Haidhar Kamarzaman (USIM Press, 2025)
The application of critical thinking in takhrij al-hadith is essential in ensuring the authenticity and reliability of hadith, particularly in contemporary Islamic studies. Takhrij al-hadith, as a methodological process of tracing the sources, chains of transmission (sanad), and textual content (matn) of hadith, requires rigorous analytical skills to assess the credibility of narrators and the consistency of transmitted reports. However, the challenge lies in the ability of researchers and scholars to apply a structured critical thinking approach to evaluate hadith comprehensively. The problem arises when certain hadith are misinterpreted or taken out of context due to the lack of a systematic method in assessing their authenticity. This study aims to explore the role of critical thinking in takhrij al-hadith, focusing on how logical reasoning, skepticism, and analytical evaluation can enhance the authentication process. The research will employ a qualitative methodology, utilizing library research, content analysis, and a comparative study of classical and contemporary hadith authentication methods. The expected findings will demonstrate that integrating critical thinking into takhrij al-hadith not only strengthens the authentication process but also minimizes the risk of misinformation and misapplication of hadith in contemporary discourse.